2001
DOI: 10.1073/pnas.251542998
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic dilation of cerebral blood vessels is abolished in M 5 muscarinic acetylcholine receptor knockout mice

Abstract: The M5 muscarinic receptor is the most recent member of the muscarinic acetylcholine receptor family (M1-M5) to be cloned. At present, the physiological relevance of this receptor subtype remains unknown, primarily because of its low expression levels and the lack of M 5 receptor-selective ligands. To circumvent these difficulties, we used gene targeting technology to generate M 5 receptor-deficient mice (M5R ؊/؊ mice). M5R ؊/؊ mice did not differ from their wild-type littermates in various behavioral and phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
208
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 53 publications
21
208
0
Order By: Relevance
“…4), a function of ACh attributed to M 5 based on receptor localization and knockout mouse experiments (31,32). Our data indicate that M 1 also regulates CBF perhaps via neurovascular coupling.…”
Section: Discussionmentioning
confidence: 61%
“…4), a function of ACh attributed to M 5 based on receptor localization and knockout mouse experiments (31,32). Our data indicate that M 1 also regulates CBF perhaps via neurovascular coupling.…”
Section: Discussionmentioning
confidence: 61%
“…Earlier studies show that muscarinic agonists potentiate DA efflux in the striatum (5)(6)(7)(8). However, other studies reported that mAChR agonists depress DA transients measured with fast-scan cyclic voltammetry (FSCV) and evoked by electrical stimulation in the striatum (9)(10)(11).…”
mentioning
confidence: 99%
“…Antisense 14,15 and gene targeting technologies have emerged as powerful new tools in identifying the receptor subtypes involved in various muscarinic cholinergic functions. [16][17][18][19][20][21] Although pharmacological, neuroanatomical and clinical studies have suggested an important role of muscarinic receptors in synaptic plasticity and memory, the functions of the individual muscarinic receptor subtypes remain unclear. In this study, we have used M2 and M4 receptor single knockout (KO) as well as M2/M4 receptor double KO mice to investigate the functional importance of M2 and M4 receptors in the regulation of acetylcholine release in the hippocampus and in cognitive processes.…”
Section: Introductionmentioning
confidence: 99%